2020
DOI: 10.3389/fimmu.2020.591088
|View full text |Cite
|
Sign up to set email alerts
|

The Oral Microbiome and Cancer

Abstract: There is mounting evidence that members of the human microbiome are highly associated with a wide variety of cancer types. Among oral cancers, oral squamous cell carcinoma (OSCC) is the most prevalent and most commonly studied, and it is the most common malignancy of the head and neck worldwide. However, there is a void regarding the role that the oral microbiome may play in OSCC. Previous studies have not consistently found a characteristic oral microbiome composition associated with OSCC. Although a direct c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
157
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(163 citation statements)
references
References 215 publications
3
157
0
3
Order By: Relevance
“…Since S. mutans is a key bacterium for the formation of dental plaques, the type of bacteriocin in S. mutans affects the composition of bacterial flora in dental plaques. To date, many investigations regarding the oral bacterial composition in saliva and dental plaque have been performed 24 28 . In particular, comparative analyses between healthy subjects and those with oral diseases, such as periodontitis, dental caries and oral cancer, have been demonstrated to identify the key bacteria or bacterial flora specific for the disease or health status.…”
Section: Discussionmentioning
confidence: 99%
“…Since S. mutans is a key bacterium for the formation of dental plaques, the type of bacteriocin in S. mutans affects the composition of bacterial flora in dental plaques. To date, many investigations regarding the oral bacterial composition in saliva and dental plaque have been performed 24 28 . In particular, comparative analyses between healthy subjects and those with oral diseases, such as periodontitis, dental caries and oral cancer, have been demonstrated to identify the key bacteria or bacterial flora specific for the disease or health status.…”
Section: Discussionmentioning
confidence: 99%
“…gingivalis , to evade host immune mechanisms enables them to survive in systemic circulation and reach distant organ sites [ 2 ]. Due to these properties, emerging evidence shows positive associations of oral bacterial pathogens not only with oral potentially malignant lesions [ 5 , 8 ] and oral or orodigestive cancers, [ 30 33 ] but also with distant cancer sites [ 1 , 34 , 35 ]. Recent meta-analysis on the effect of periodontal bacteria infection on incidence and prognosis of cancer confirmed that P .…”
Section: Discussionmentioning
confidence: 99%
“…The ability of these pathogens, particularly P. gingivalis, to evade host immune mechanisms enables them to survive in systemic circulation and reach distant organ sites [2]. Due to these properties, emerging evidence shows positive associations of oral bacterial pathogens not only with oral potentially malignant lesions [5,8] and oral or orodigestive cancers, [30][31][32][33] but also with distant cancer sites [1,34,35]. Recent meta-analysis on the effect of periodontal bacteria infection on incidence and prognosis of cancer confirmed that P.gingivalis and P.intermedia infection was associated with high incidence of cancer and P.gingivalis and F. nucleatum infection was associated with poor prognosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…An increased risk of developing oral squamous cell carcinoma (OSCC) associated with periodontitis suggests a possible role of inflammation caused by the microbiome with oral cancer. Periodontitis is a typical example of an infectious disease causing chronic inflammation in the oral cavity [56]. Recent evidence proved the role of microbiomederived signals in the pathogenesis of several chronic inflammatory diseases.…”
Section: Correlation Between Oral Microbiome Chronic Inflammation and Hpv Infectionmentioning
confidence: 99%
“…Chronic infection with P. gingivalis and Fusobacterium nucleatum has been recently demonstrated to promote tongue tumors in a murine model through direct interaction with oral epithelial cells, leading to upregulation of the IL-6-STAT3 pathway in a TLR2-dependent manner [56]. P. gingivalis was also shown to cause gingival epithelial cells (GECs) to migrate in a manner which depends on the overexpression of Zeb1, an activator of the epithelial-mesenchymal transition (EMT).…”
Section: Correlation Between Oral Microbiome Chronic Inflammation and Hpv Infectionmentioning
confidence: 99%